The Basic Science of Patient–Physician Communication: A Critical Scoping Review. (27th October 2021) - Forsey, Jacquelin; Ng, Stella; Rowland, Paula; Freeman, Risa; Li, Connie; Woods, Nicole N.
Abstract : Purpose: Strong verbal communication skills are essential for physicians. Despite a wealth of medical education research exploring communication skills training, learners struggle to become strong communicators. Integrating basic science into the curriculum provides students with conceptual knowledge that improves learning outcomes and facilitates the development of adaptive expertise, but the conceptual knowledge, or "basic science, " of patient–provider communication is currently unknown. This review sought to address that gap and identify conceptual knowledge that would support improved communication skills training for medical trainees. Method: Combining the search methodology of Arksey and O'Malley with a critical analytical lens, the authors conducted a critical scoping review of literature in linguistics, cognitive psychology, and communications to determine: what is known about verbal communication at the level of word choice in physician–patient interactions? Studies were independently screened by 3 researchers during 2 rounds of review. Data extraction focused on theoretical contributions associated with language use and variation. Analysis linked patterns of language use to broader theoretical constructs across disciplines. Results: The initial search returned 15, 851 unique studies, and 271 studies were included in the review. The dominant conceptual groupings reflected in the results were: (1) clear and explicit language, (2) patient participation and activation, (3) negotiating epistemic knowledge, (4) affiliative language and emotional bonds, (5) role and identity, and (6) managing transactional and relational goals. Conclusions: This in-depth exploration supports and contextualizes theory-driven research of physician–patient communication. The findings may be used to support future communications research in this field and educational innovations based on a solid theoretical foundation.